Association of periodontitis with serum osteoprotegerin level in type 2 diabetic postmenopausal women - Dalia Kudier Abbas; Abdulkareem Hamady Issa (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate the association of periodontitis with serum osteoprotegerin level according to glycaemic state in postmenopausal type 2 diabetic women. Method: The case-control study was conducted from June 2019 to May 2020 at the National Diabetes Centre, Mustansiriyah University, Baghdad, Iraq, and comprised postmenopausal diabetic women with good glycaemic control in group A, diabetic women with poor glycaemic control in group B, and non-diabetic healthy controls in group C. Participants were inducted by using the consecutive sampling technique. Assessment of periodontitis was done by measuring probing pocket depth, gingival recession and clinical attachment level. The ratio between serum osteoprotegerin level and glycated haemoglobin was calculated for all the subjects. Data was analysed using SPSS 24. Results: Of the 150 subjects, 57(38%) were in group A with mean age 57.39±5.89 years, 43(28.7%) were in group B with mean age 58.91±4.95 years, and 50(33.3%) 57(%) were in group C with mean age 54.92±4.62 years. Probing pocket depth, clinical attachment level and serum osteoprotegerin exhibited higher values in groups A and B compared to group C, and in group B compared to group A (p<0.001). There was a significant positive correlation between Probing pocket depth and serum osteoprotegerin in all groups (p<0.05). Conclusion: Periodontal parameters and serum osteoprotegerin level were significantly higher in diabetic women, especially in those with poor glycaemic control, than in healthy controls, and serum osteoprotegerin level showed a significant positive correlation with probing pocket depth in all the studied groups. Key Words: Glycated Haemoglobin, Osteoprotegerin, Gingival Recession, Glycaemic, Postmenopausal, Diabetes